Vpletenost vrstnikov v izobraževanje študentov - Zlatka Cugmas; Eva Kranjec (Journal of Elementary Education, 2016)
Peer Involvement in University Students’ Education. We investigated the correlations between peer involvement in students’ education and their self-perception, attachment style, relationships with peers, personality and well-being. We used the Inventory of parent and peer attachment (Armsden & Greenberg, 1987), Relationship questionnaire (Bartholomew & Horowitz, 1991), Questionnaire of the subjects’ self-perceptions (Cugmas, 2012) and The big five questionnaire (BFQ; Caprara et al, 2002). We developed the questionnaires of peer involvement and subjects’ well-being. Positive relationships with peers, secure attachment style, positive self-perceptions, some personal characteristics and well-being were positively associated with peer support, and negatively with peer pressure.